Functionalization of 68Ga-Radiolabeled Nanodiamonds with Octreotide Does Not Improve Tumor-Targeting Capabilities - Thomas Wanek; Marco Raabe; Md Noor A Alam; Thomas Filip; Johann Stanek; Mathilde Loebsch; Christian Laube; Severin Mairinger; Tanja Weil; Claudia Kuntner (MDPI AG, 2024)
Nanodiamonds (NDs) are emerging as a novel nanoparticle class with growing interest in medical applications. The surface coating of NDs can be modified by attaching binding ligands or imaging probes, turning them into multi-modal targeting agents. In this investigation, we assessed the targeting efficacy of octreotide-functionalized 68Ga-radiolabelled NDs for cancer imaging and compared it with the tumor uptake using [68Ga]Ga-DOTA-TOC. In vivo studies in mice bearing AR42J tumors demonstrated the highest accumulation of the radiolabeled functionalized NDs in the liver and spleen, with relatively low tumor uptake compared to [68Ga]Ga-DOTA-TOC. Our findings suggest that, within the scope of this study, functionalization did not enhance the tumor-targeting capabilities of NDs.